Tren Belanja Online Pada Masyarakat Kota Palembang Masa Pandemi Covid 19 (Analisis Perilaku Konsumen Perspektif Ekonomi Islam) - Melis Melis (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
This paper aims to explain Islamic economic theory about consumption and consumer behavior, and later this paper will also explain the behavior of the people of Palembang City in shopping online during the Covid-19 Pandemic. This paper uses a qualitative approach. The data obtained from the literature study, namely from various sources of books on consumption in the perspective of Islamic economics. As a result, the online shopping trend of the people of Palembang city is in accordance with the corridors of Islamic law, namely the consumption principle from an Islamic economic perspective. In the concept of Islamic consumption, there are moral and social values (maslahah) which recognize the rights of others in meeting individual needs, the allocation of personal assets for zakat, infaq, shadaqah, and other benefits that are set aside by Muslim consumers in every fulfillment of their needs.Keywords: Online Shopping; Consumption; Consumer Behavior; Islamic Economy AbstrakTulisan ini bertujuan untuk menjelaskan teori ekonomi Islam tentang konsumsi dan perilaku konsumen, dan nantinya tulisan ini juga akan menjelaskan perilaku masyarakat Kota Palembang dalam berbelanja online di masa Pandemi Covid-19. Tulisan ini menggunakan pendekatan kualitatif. Data-data yang didapatkan dari studi kepustakaan, yakni dari berbagai sumber buku tentang konsumsi dalam perspektif ekonomi Islam. Hasilnya, tren belanja online masyarakat kota Palembang sesuai dengan koridor syariat Islam, yakni dalam prinsip konsumsi perpektif ekonomi Islam. Dalam konsep konsumsi Islam terkandung nilai-nilai moral dan sosial (maslahah) yang mengakui hak orang lain dalam pemenuhan kebutuhan individu, adanya pengalokasian harta pribadi untuk zakat, infaq, shadaqah, dan kemaslahatan lain yang disisihkan konsumen muslim dalam setiap pemenuhan kebutuhan yang dilakukannya.Kata kunci: Belanja Online; Konsumsi; Perilaku Konsumen; Ekonomi Islam